Preventing facial pressure injuries among health care staff working in diverse COVID‐19 care environments. Issue 7 (10th February 2022) - Moore, Zena; Moore, David; McEvoy, Natalie L.; Avsar, Pinar; O'Connor, Tom; Budri, Aglecia; Curley, Gerard; Walsh, Simone; Burke, Frank; Porter‐Armstrong, Alison; Chaboyer, Wendy; Rice, John; et al.
Abstract: The aim of this study was to determine the impact of a specially designed care bundle on the development of facial pressure injuries among frontline health care workers wearing personal protective equipment (PPE) during the COVID‐19 pandemic. This was a mixed methods study. First, a pre‐posttest observational design was employed to evaluate the impact of the pre‐piloted intervention, a care bundle including skin cleansing and hydration, protective material use, facemask selection and skin inspection, developed in line with international best practice guidelines. Data were collected using survey methodology. Frontline COVID‐19 staff working in acute, community and ambulance services were invited to participate. Then, judgemental and volunteer sampling was used to select participants to undertake semi‐structured interviews to elicit feedback on their perceptions of the care bundle. The sample included 120 acute hospital staff, 60 Ambulance staff, 24 Community Hub staff and 20 COVID‐19 testing centre staff. A survey response rate of 61% was realised (n = 135/224). Of the participants, 32% (n = 43) had a facial pressure ulcer (FPI) pre‐intervention and 13% (n = 18) developed an FPI while using the care bundle. The odds ratio (OR) was 0.33 (95% CI: 0.18 to 0.61; P = .0004), indicating a 77% reduction in the odds of FPI development with use of the care bundle. Analysis of the qualitative data from 22 interviews identified three key themes, the context for the care bundle, the ease of use of the care bundle and the care bundle as a solution to FPI development. The care bundle reduced the incidence of FPI among the participants and was found to be easy to use. Implementation of skin protection for frontline staff continues to be important given the persistently high incidence of COVID‐19 and the ongoing need to wear PPE for protracted durations.